The Possible Role of Probiotics in Combating COVID-19 - Guntur Darmawan; Marshell Tendean; Ade Dharmawan; William William; Henny Tannady Tan; Tamara Atmogo; Wani Devita Gunardi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
Since first reported in Wuhan in the end of 2019, COVID-19 infection has spread globally. However, our battle against COVID-19 is still limited with treatment modalities, yet giving a big challenge for researchers to explore promising treatment candidate. Probiotics, based on previous studies of its role in immune system and respiratory tract infection, seem to be potential candidate. Probiotics work in a distinct way through connectivity between gut and the lung, since both have expression of angiotensin converting enzyme2 (ACE2) of which highly bound by COVID-19. At present, no guidelines formally include probiotics as part of COVID-19 treatment. Hence, this study aimed to review the link of probiotics and immune system and its potential role as part of COVID-19 treatment.